Ultrafast gelation of silk fibroin-assisted conductive hydrogel with long-term environmental stability using self-catalytic dopamine/metal/H2O2 system. (5th September 2022) - Bao, Xueming; Yan, Biaobiao; Yu, Yuanyuan; Xu, Bo; Cui, Li; Zhou, Man; Wang, Qiang; Wang, Ping
Graphical abstract: Highlights: Dopamine-Fe 3+ –H2 O2 redox system rapidly initiated the polymerization of acrylic acid at low temperature. An anti-freezing organo-hydrogel containing glycerol was successfully fabricated within a short time (40 s). Silk fibroin enhanced the structural integrity of organo-hydrogel via dopamine-catalyzed co-coupling. Dopamine-Fe 3+ self-catalysis endows the composite hydrogels with multifunctional capabilities. Abstract: Anti-freezing organo-hydrogels gain great popularity for their excellent performances at subzero temperatures. However, the traditional fabrication of such gels always requires a complex process with external stimuli like high temperature and additional catalysts, bringing inconvenience and restrictions in large-scale applications. Hence, inspired by the mussel-inspired catechol-based chemistry, a novel, green and ultrafast self-catalysis initiation system is established by the special redox equilibrium among dopamine (DA), iron (Fe 3+ ) and hydrogen peroxide (H2 O2 ) with multi-functional capabilities. The ternary DA-Fe 3+ –H2 O2 complex generated plentiful hydroxyl radicals to initiate the rapid polymerization of acrylic acid (AA) with oxygen tolerance. Simultaneously, silk fibroin (SF) as a natural bio-material was employed to enhance the structural integrity of the PAA network, via dopamine-initiated co-coupling of tyramine residues from silk fibroin (SF) chains with the vinyl radicals within 40 s at a low temperature. Moreover, the introduction of DA-Fe 3+ pair provides the obtained organo-hydrogel fascinating UV-blocking, good adhesion property to a variety of materials, companying with encouraging conductivity, while the glycerol-water dual phase endows the organo-hydrogel with intriguing environmental stability, like anti-freezing and anti-drying properties. The present work expands the potential of dopamine-based self-catalysis in polymerization of various monomers and its application in construction of diverse gel-like multi-functional materials as well.